Corruption, economic growth and the informal sector: Empirical evidence from developing countries - Ibrahim Ngouhouo; Loudi Njoya; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
The main objective of this paper is to contribute to in-depth literature on the relationship between growth and the informal sector in the presence of corruption. The impact of the interaction between growth and corruption on economic performance (increase or decrease of the informal sector) will be discussed. To the best of our knowledge, our paper is unique in the empirical literature because it studies the effect of the interaction between growth and corruption in the informal sector using a sample of developing countries. Our results based on the FE, system GMM, MG, AMG, and IV-2SLS for 112 countries between the 1991- 2015 periods, show that growth reduces informality in the direct effect regression. Moreover, economic growth interacts with corruption and produces negative net effects up to a corruption threshold of 4.79745 when this effect is nullified. This negative net effect was found to be robust across different regional groupings and income groups except in the Middle East and North Africa (positive net effect) and high income and upper-middleincome countries (only direct effects) producing different thresholds per sample. The study recommends that policymakers should intensify their fight against corruption in their quest to reduce the size of the informal economy.
Keywords: D73; F47; J46; O1; O17; O47; 330; Informal sector; Growth; Corruption; Developing countries